Educational Institutions: Policies and Priorities in Preparing Human Resources - Manti, Biltiser Bachtiar; Bayu, Yunus (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2025)
This article attempts to clarify the relationship between educational institutions and increasing human resource competitiveness in the era of Society 5.0. However, to strengthen the focus and relevance of the research, it is important to link the role of educational institutions with the characteristics of Society 5.0, such as the need for innovation, multifunctional collaboration, and adaptability to technology. This can help show how education can prepare individuals to be more competitive in an increasingly integrated and technology-based society. Therefore, policy and planning steps are needed in building national education, including 1. Committing to mastering basic literacy and numeracy skills, 2) Measuring learning regularly, accurately, and relevantly, 3) Aligning the system with learning commitments, 4) Supporting teachers in the teaching and learning process. 5) Adapting approaches in making educational policies. Support in adapting policies so that they are in accordance with the local context. The Central Government needs to map out areas that need extra assistance so that the policies that are created can focus on improving quality learning. Meanwhile, local governments can also collaborate with other elements of society, such as grassroots organizations and the private sector, in designing and implementing educational innovations.